Pengaruh Konsentrasi Asam Stearat Sebagai Emulsifying Agent Terhadap Karakteristik Fisik Sediaan Krim Ekstrak Daun Pepaya (Carica Papaya L.) - Ika Windi Sepriliani; Sisca Devi (Indonesian Journal on Medical Science, 2022)
Acne is one of the most common skin problems. Plants that can be used to treat acne are papaya plants, especially the leaves. Cream is a topical dosage form with a semi-solid form suitable for the treatment of acne. The purpose of this study was to determine the effect of stearic acid concentration as an emulsifying agent on the physical characteristics of papaya leaf extract cream preparations. The type of research carried out is an experimental study using a completely randomized design with one factor, namely the concentration of stearic acid, by testing the physical characteristics of organoleptic, homogeneity, pH, adhesion, spreadability, cream type, viscosity, protection power, and washability. The test results were analyzed using the ANOVA test. The effect of stearic acid concentration on all tests shown no effect on organoleptic, homogeneity, and type of papaya leaf extract cream. The results of all statistical tests yielded p value <0.05 which indicates the difference in the meaning of each formula.